FINANCIAL MANAGEMENT PRACTICES AND FINANCIAL PERFORMANCE OF SMALL SCALE BUSINESSES IN BUGUJJU, MUKONO. - Asiimire Amanda (Uganda Christian University, 2024)
This research report established the connection between financial management practices and financial performance of small-scale businesses in Bugujju village in Mukono district. It focused on the objectives; to establish the effect of budgeting on the financial performance of small scale businesses, to find out the influence of risk management on financial performance of small scale businesses. And to analyze the relationship between cash flow management and financial performance of small scale businesses. The report provides background information for this research, including the problem statement, objectives and purpose. It describes the research questions, the extent of the study, and its relevance in chapter 1. Chapter 2 provides an overview of the literature study on financial management techniques and financial success in small enterprises, as well as how different researchers have evaluated these variables. Chapter 3 presents the research methodology. This includes the research design which was cross-sectional research design, study population of 60, sample size of 52, data collection instruments which was a questionnaire, data quality (reliability and validity), and data presentation methods. Chapter 4 discusses the research findings in relation to the research objectives. The study found out that small firms can achieve success, profit, and business expansion through effective financial management practices. Well-established financial management practices such as budgeting, risk management and cash flow management assist managers in predicting future financial needs and trends as well as helping them comprehend the financial status of the company at a given moment. Data was provided in a tabular format to enhance clarity and easy of interpretation.